2023
DOI: 10.3201/eid2908.230403
|View full text |Cite
|
Sign up to set email alerts
|

Infected Aneurysm Caused by Desulfovibrio desulfuricans Infection

Abstract: An 84-year-old man in Japan who had undergone endovascular aortic repair 9 years earlier had an infected aneurysm develop. We detected Desulfovibrio desulfuricans MB at the site. The patient recovered after surgical debridement, artificial vessel replacement, and appropriate antimicrobial therapy. Clinicians should suspect Desulfovibrio spp. infection in similar cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A prior investigation revealed that Desulfocibrio desulfuricans could contribute to aneurysm infections ( Fujihara et al, 2023 ). Additionally, another study noted that the order Desulfovibrionales and the family Desulfovibrionaceae were linked to an increased risk of chronic obstructive pulmonary disease ( Wei et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A prior investigation revealed that Desulfocibrio desulfuricans could contribute to aneurysm infections ( Fujihara et al, 2023 ). Additionally, another study noted that the order Desulfovibrionales and the family Desulfovibrionaceae were linked to an increased risk of chronic obstructive pulmonary disease ( Wei et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%